South Korea's rise economic development, power, and foreign relations - Heo, Uk 1962-; Roehrig, Terence 1955- (Cambridge Cambridge University Press, 2014)
"South Korea's phenomenal rise has been studied extensively by political scientists and economists both in terms of its impact on democratization and as a role model for economic development. Yet little attention has been devoted to exploring the nexus between economic development and foreign policy. In South Korea's Rise, Uk Heo and Terence Roehrig propose a new theoretical framework to illustrate how an increase in a country's economic prosperity can bring about change to its foreign policy, prompting greater involvement in the international system, the transition to democracy, an expanded set of interests and increased tools to pursue its foreign policy goals. As a rising middle power, analysis of South Korea's foreign policy is crucial to our understanding of the power structure and future relations in East Asia. This is essential reading for all students and scholars with an interest in Asia, foreign policy and global economics".
Introduction -- Economic development, state power and foreign policy -- Inter-Korean relations : confrontation, economic exchanges, and the nuclear crisis -- South Korea and the United States : from dependency to partnership -- South Korea, Russia, and China : from adversaries to economic partners -- South Korea and Japan : an ambivalent relationship -- South Korea and the European Union : evolving cooperation and competition -- South Korea and India -- South Korea and the developing world : Africa, Latin America, the Middle East and Southeast Asia -- Contributing to the international community : from consumer to producer -- Conclusion.
Includes bibliographical references and index.
Keywords: Korea (South) -- Foreign relations -- 2002-.; Korea (South) -- Foreign economic relations; Korea (South) -- Economic conditions -- 21st century